A case control study on behavioural risk factors client with ischemic heart disease of selected cardiac hospitals of Kathmandu district. - Shrestha,Sangita (2015)
ABSTRACT: Ischemic Heart Disease (IHD) is the first cause of morbidity and mortality among the in- patient of different cardiac hospital. The prevalence of CHD was 5.7% with significant associated risk factors included tobacco use, history of hypertension, family history and age. Therefore, in order to prevent IHD this study was conducted to determine the risk factors for IHD. The study used hospital - based pair match case-control design. Clients with IHD attending inpatient at Manmohan Cardiothoracic Vascular and Transplant Centre and Shahid Gangalal National Heart Center were taken as cases, and controls included two age (± 2 years) and sex matched clients for each case from the same hospitals. Non-random purposive sampling technique was applied and sample size was 105 (35 cases and 70 controls. Majority (88.6% cases and 90% controls) respondents were belongs to 41 and above years and IHD was more common in males (60%) than in female (40%). Analysis using Chi-square, Fisher's exact and odds ratio identify current smoking (OR=3.115, p=0.035), work related vigorous intense activity (OR=12.667, p=0.003), work related moderate-intense activity (OR=2.276, p=0.049), hypertension (OR=2.538, p=0.026), obesity (OR=2.44, p=0.045) and waist to hip ratio (OR=2.88,p=0.013) to be significantly associated with IHD. Clients who currently smoke are three times more likely to develop IHD, who were not doing work-related vigorous-intense activity are 13 times at greater risk of having IHD. Clients who were not doing work-related moderate-intense activity are two times, who were hypertensive are two times, who were obese are three times and whose waist to hip ratio are three times more likely of IHD. In order to reduce the burden of complex and extensive IHD treatment minimizing exposure to the identified risk factors is essential thus the findings obtained through data need to keep in mind by the nurses, educators and managers in health care settings. This in turn ultimately results in reduction of morbidity and mortality due to IHD.